2001
DOI: 10.1002/jccs.200100178
|View full text |Cite
|
Sign up to set email alerts
|

Simple Fourier Trans form(FT)‐IR and Reverse‐Phase HPLC Identification Methods of Commercial Ganoderma Products

Abstract: Ganoderma products could be classified into 3 types according to their raw materials, i.e. fruit bodies, cultured mycelia and the mixtures of both. Seven commercial samples and three mycelia products prepared in laboratory were analyzed by Fourier Trans form(FT)‐IR spectrophotometer. The fruit‐body products gave a weak absorption band at 890∼894 cm−1 and the mycelia show a weak to medium band at 774∼778 cm−1 on the FT‐IR spectra, respectively. These two bands were observed in the IR spectra of mixed‐type produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this work, the reversed-phase (RP)-HPLC profiles of extracted triterpenoids from G. lucidum were found to be similar between the use of conventional solvent extraction and Sep-Pak C 18 cartridge extraction methods, with the latter method requiring significantly less time and volumes of organic solvents. In a more recent study [54], the use of a C 18 Sep-Pak cartridge for rapid and efficient sample pretreatment prior to the RP-HPLC separation of various triterpenoids present in seven commercial Ganoderma products were also reported. To further reduce the consumption of organic solvents, the use of supercritical CO 2 (with a small amount of ethanol added as modifier) has been demonstrated to be an environmentally friendly and effective approach for the extraction of triterpenes from G. lucidum [55], with higher extraction yield and lower extraction temperature compared to those of conventional extraction methods.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the reversed-phase (RP)-HPLC profiles of extracted triterpenoids from G. lucidum were found to be similar between the use of conventional solvent extraction and Sep-Pak C 18 cartridge extraction methods, with the latter method requiring significantly less time and volumes of organic solvents. In a more recent study [54], the use of a C 18 Sep-Pak cartridge for rapid and efficient sample pretreatment prior to the RP-HPLC separation of various triterpenoids present in seven commercial Ganoderma products were also reported. To further reduce the consumption of organic solvents, the use of supercritical CO 2 (with a small amount of ethanol added as modifier) has been demonstrated to be an environmentally friendly and effective approach for the extraction of triterpenes from G. lucidum [55], with higher extraction yield and lower extraction temperature compared to those of conventional extraction methods.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…For the rapid and efficient characterization of Lingzhi, Sye [53] reported that triterpenoid patterns obtained from different strains of G. lucidum can be obtained by RP-HPLC based on the use of a small Sep-Pak C 18 cartridge for the extraction of ganoderic acids. In a study by Chen et al [54], various strains of Ganoderma belonging to G. tsugae and G. lucidum were cultivated and the triterpenoid patterns of their fruiting bodies were obtained by RP-HPLC using a gradient of acetonitrile and 2% acetic acid. In another study, Chen et al [66] reported the use of spectral analysis based on simple Fourier transform infrared absorption as well as RP-HPLC, with isocratic elution using acetonitrile-2% acetic acid (1:2), for the classification/identification of various commercial Ganoderma products (G. lucidum and G. tsugae) into three different types: cultured mycelia, fruiting bodies and mixed mycelia/fruiting bodies.…”
Section: Hplc Profiling Of Triterpenes/triterpenoids and Quality Contmentioning
confidence: 99%